Assessing the Role of Islamic Microfinance on Poverty - Abdul Holik (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2026)
The Contribution of Islamic microfinance to reducing poverty is sometimes questionable. This research aims to answer that doubt by finding its impact empirically. We use secondary data from Bank Indonesia and Financial Service Authority (Otoritas Jasa Keuangan), namely the number of BPRS and financing of BPRS, and the number of poor people. Based on the results of OLS (Ordinary Least Squares), we obtain that the number of BPRS has a significant negative impact on poverty. However, variable financing of BPRS does not show a significant impact. Meanwhile, the result of Granger-Causality test reveals that financing of BPRS has a significant impact on poverty. Meanwhile, the number of BPRS does not show any significant influence at all. It seems like a contradiction between the analysis of OLS dan Granger-Causality test. Nevertheless, from this finding, we can conclude that the existence of BPRS has a vital role in boosting micro, small, and medium businesses in society, especially among the poor. BPRS, as the Islamic microfinance intitutions provides credit for unbankable people and supports financial inclusion.